2015
DOI: 10.1109/jphotov.2015.2437272
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Optical Properties of APCVD Titanium Oxide Films for All-Oxide Multilayer Antireflection Coatings

Abstract: In this paper, the optical properties and microstructure of titanium oxide (TiO x ) thin films deposited by in-line atmospheric pressure chemical vapor deposition (APCVD) are tailored to act as effective antireflection coatings (ARCs) in crystalline silicon solar cells. The ability to control the crystalline phase, microstructure, and optical properties of these TiO x films by varying the deposition conditions is demonstrated. Because the refractive index of TiO x can be widely varied by changing the depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…They showed S eff of 3.88 cm s −1 in 1 Ωcm n‐type silicon when the film was extrinsically charged using corona. In particular they showed that the films optical properties can be tailored in APCVD deposition, as previously shown by Davis et al , while passivation properties are modified post‐deposition by additional processing. A summary of the best performing passivating titanium oxide films is shown in Table .…”
Section: Materials and Methods For Silicon Surface Passivationmentioning
confidence: 56%
See 1 more Smart Citation
“…They showed S eff of 3.88 cm s −1 in 1 Ωcm n‐type silicon when the film was extrinsically charged using corona. In particular they showed that the films optical properties can be tailored in APCVD deposition, as previously shown by Davis et al , while passivation properties are modified post‐deposition by additional processing. A summary of the best performing passivating titanium oxide films is shown in Table .…”
Section: Materials and Methods For Silicon Surface Passivationmentioning
confidence: 56%
“…TiO x showed optimal optical properties to act as an antireflection coating between a silicon surface and an Ethylene Vinyl Acetate (EVA) encapsulant film used when packing cells into modules . The ideal refractive index for the top antireflection layer in encapsulated cell is ∼2.1 at λ = 630 nm . Deposition of TiO x was performed using either chemical or physical vapour techniques , and its use extended beyond that of the solar industry, most prominently in glass manufacturing as a protection coating deposited using ultra‐high throughput techniques .…”
Section: Materials and Methods For Silicon Surface Passivationmentioning
confidence: 99%
“…Aperiodic photonic thin-film mirrors are designed and simulated with the common dielectric materials SiO 2 , Si 3 N 4 , TiO 2 , and Al 2 O 3 (see Figure S1 in the Supporting Information). Superstrate and substrate indices for the cover glass and EVA are taken from refs and , respectively, while for air we take n = 1.…”
Section: Methodsmentioning
confidence: 99%
“…7c shows absorption obtained by FDTD simulation. In the simulation, we have used refractive index and extinction coefficient for TiO 2 from reference [29] and Ag (CRC) from FDTD software [30]. The monitor was placed at a distance of 10 nm from the top surface of the thin film.…”
Section: Absorption Spectroscopy and Fdtd Simulationmentioning
confidence: 99%